Achieving Excellence in Graduate Research: A Guide for New Graduate Students. Issue 10 (17th July 2015) - Parker, Charles B.; Amsden, Jason J.; Peng, Qing; Stoner, Brian R.; Glass, Jeffrey T.
<x xml:space="preserve">Abstract</x> A mentoring guide for incoming graduate students has been developed to minimize the time spent reiterating general guidance and "norms" that need to be instilled in new graduate students. This allows principal investigators and senior researchers to provide high value, customized coaching for the individual student which is where the real value of the PhD education is expressed.